EMG Based Serious Game For Use in Stroke Rehabilitation - Silva, Gabriel R.; Guerra, Rodrigo da S. (Anais Estendidos do Simpósio Brasileiro de Jogos e Entretenimento Digital (SBGames); 2023: Anais Estendidos do XXII Simpósio Brasileiro de Jogos e Entretenimento Digital, 2023)
This paper introduces a proof-of-concept for a serious game that uses electromyography (EMG) signals as input, with the aim of improving rehabilitation treatment for patients experiencing stroke sequelae. The prototype, developed with the Unity game engine, incorporates a low-cost hardware device for reading and processing EMG signals. Communication between software and sensor is enabled through Bluetooth using an ESP32 microcontroller. The prototype includes a secondary monitor with a virtual hand to emulate Mirror Therapy. The positive evaluation of a physiotherapist validates the project for future development.